Processing of word formation in primary school on the example of individual lexemes in the poetry of Milosav Tesic - Raković Marija S. (University of Kragujevac - Faculty of Pedagogy, Užice, 2021)
The subject of the paper is a methodical approach to word formation in primary school on the example of Milosav Tesic's poetry. The aim is to determine the models of formation of lexemes marked with the label individually and to give methodical recommendations for the incorporation of the analyzed models of formation in the teaching process. The creative analysis includes lexemes that represent: (1) the individual work of the poet and (2) standard language lexemes to which the poet gave a new meaning, not recorded in the RMS. The corpus was made on the basis of an insight into the anthological collection entitled U tesnom skpopu, as well as on the basis of critical texts by A. Petrovic. The creative analysis came to the conclusion that the largest number of individualisms was created by agreement, and the most numerous products are semi-complex, so these models can be examples to show these models of creation in primary school. A brief review of the work is given in order to show the poet's treatment of the mother tongue with special attention with the constant creation of new words which re-creates and renews his poetry, as well as to justify in some way the suitability of the topic for creative and semantic research. Serbian, and thus as interesting and easy to remember examples of word formation in primary school. Based on the conducted analysis, pedagogical implications for teaching practice will be given, which concern: (1) the possibility of processing word formation models in primary school and (2) examples of tasks for practicing the acquired knowledge.